A deep outer‐rise reverse‐fault earthquake immediately triggered a shallow normal‐fault earthquake: The 7 December 2012 off‐Sanriku earthquake (MW 7.3). Issue 16 (22nd August 2013) - Harada, Tomoya; Murotani, Satoko; Satake, Kenji
Abstract [1] Teleseismic body wave analysis revealed that the 7 December 2012 off‐Sanriku earthquake (MW 7.3) at the outer rise of Japan Trench consisted of two successive subevents. The first subevent with reverse‐fault mechanism (Event 1, MW 7.1) at 56 km depth was followed by, approximately 20 s later, the second subevent with normal‐fault mechanism (Event 2, MW 7.2) at 6 km depth. Finite‐fault slip models show that the slip of Event 1 was concentrated around the initial rupture point with the maximum of 2.7 m and that Event 2 had two asperities with the maximum of 4.5 m at both sides of the initial rupture point. The static Coulomb Failure Function analyses suggested that Event 1 triggered Event 2 and that both subevents were promoted by the 2011 Tohoku earthquake (MW 9.1).